Deploying street outreach workers to reduce failure to appear in juvenile court for youth of color: a randomized study - Cusworth Walker, Sarah (Crime & delinquency, 2019)
This study is a randomized controlled trial of a failure to appear (FTA) prevention program involving street outreach workers. Over 2 years, 560 youth were randomized to receive street outreach services or no services based on an FTA risk score. The program was found to significantly and modestly reduce the likelihood of an FTA at the first court hearing following a summons (arraignment) but not subsequent hearings (case setting). No interactions were found for differential effects by race/ethnicity or gender. Although the program prioritized youth of color, the effects were not sufficient to substantially reduce disparities given the dispersed benefits to all youth. Implications of these findings for reducing race and ethnic disparities are discussed.